Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.15381/rpb.v15i3.3772
|View full text |Cite
|
Sign up to set email alerts
|

American palms used for medicine, in the ethnobotanical and pharmacological publications

Abstract: The center of diversity of palms (Arecaceae) in tropical America is found in the Amazon basin and along the Panamanian isthmus.The greatest palm species richness has been reported for the Iquitos and Chocó areas. Many species of palms are used mainly for construction and due to their edible fruits. In addition, there are 104 palm species that are used for medicinal purposes in many regions of the Americas. Cocos nuciferaand Oenocarpus batauaare the most commonly used species for medicinal purposes. The fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Preparations from the fruit and other parts of E. oleracea are also abundantly used in various traditional medical practices in different parts of the world including Suriname. A few indications are anemia, hypotension, various types of wounds including open cuts, scorpion stings, and shot wounds; and as an external contraceptive [77,78,[116][117][118][119][120]. Pharmacological studies with particularly the fruit juice have shown a wide range of activities, including antidiarrheal, anti-inflammatory, antinociceptive, antiangiogenic, antimicrobial, antileishmanial, skin regenerating and antiageing, cosmeceutical, neuroprotective, anticancer, and antioxidant effects [79, [119][120][121][122].…”
Section: Antioxidant Phenolic Compounds: Anthocyanins: Euterpe Olerac...mentioning
confidence: 99%
“…Preparations from the fruit and other parts of E. oleracea are also abundantly used in various traditional medical practices in different parts of the world including Suriname. A few indications are anemia, hypotension, various types of wounds including open cuts, scorpion stings, and shot wounds; and as an external contraceptive [77,78,[116][117][118][119][120]. Pharmacological studies with particularly the fruit juice have shown a wide range of activities, including antidiarrheal, anti-inflammatory, antinociceptive, antiangiogenic, antimicrobial, antileishmanial, skin regenerating and antiageing, cosmeceutical, neuroprotective, anticancer, and antioxidant effects [79, [119][120][121][122].…”
Section: Antioxidant Phenolic Compounds: Anthocyanins: Euterpe Olerac...mentioning
confidence: 99%